2010
DOI: 10.1111/j.1365-2648.2010.05441.x
|View full text |Cite
|
Sign up to set email alerts
|

Family presence preference when patients are receiving resuscitation in an accident and emergency department

Abstract: Variations among the contributing determinants to each family member's preference to be present were revealed. Appropriate nursing interventions, policy and guidelines should be developed to meet individualized needs during such critical and life-threatening moments in accident and emergency departments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 38 publications
1
52
0
11
Order By: Relevance
“…Estudo realizado na China junto a 18 familiares de pacientes atendidos em uma unidade de emergência traumatológica constatou que nenhum dos membros da família pode acompanhar as intervenções de manutenção da vida. Contudo, a maioria indicou forte preferência por estar presente se fosse facultada essa opção, o que decorria da ligação emocional entre paciente e família (15).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Estudo realizado na China junto a 18 familiares de pacientes atendidos em uma unidade de emergência traumatológica constatou que nenhum dos membros da família pode acompanhar as intervenções de manutenção da vida. Contudo, a maioria indicou forte preferência por estar presente se fosse facultada essa opção, o que decorria da ligação emocional entre paciente e família (15).…”
Section: Discussionunclassified
“…Estudos realizados em diversos países como Estados Unidos (13)(14), China (15), Austrália (16) e Finlândia (17) têm sugerido que a família gostaria de estar presente durante o atendimento emergencial e que isso representa a construção de confiança entre família e profissionais de saúde, atende às necessidades informacionais da família e permite que seus membros se aproximem do paciente apoiando-o emocionalmente, o que em última instância aumenta a satisfação dos sujeitos com o serviço de saúde (13)(14)(15)(16)(17).…”
Section: Introductionunclassified
“…The four themes found and identified for this review indicated priorities for family members during resuscitation event and all of them relate to family member expectations of healthcare professionals (Wagner 2004;Leske et al, 2013;Hung and Pang, 2011;Weslien et al, 2006). There were no studies found that examined the pre-hospital or out of hospital care of patients and the findings related entirely to the in-hospital perspective.…”
Section: Resultsmentioning
confidence: 95%
“…The justifications to exclude these individuals are fundamentally centered in the fear that the relatives may lose their emotional control, interfering in the assistance provided and/or that the families suffer from psychologically stressing memories related to care, specially when the outcomes are unfavorable (death/sequels) (14,16) . However, it is important to consider that the families, when experiencing and acute and serious illness of one of their own, show the necessity to be present (17) . A phenomenological study performed in Hong Kong, with 18 relatives of patients who were seriously ill -relatives who never were present in any other life-sustaining intervention, showed that the majority indicated a strong preference to be present if the option was given to them.…”
Section: Discussionmentioning
confidence: 99%
“…A phenomenological study performed in Hong Kong, with 18 relatives of patients who were seriously ill -relatives who never were present in any other life-sustaining intervention, showed that the majority indicated a strong preference to be present if the option was given to them. According to the interviewees, there was a strong emotional connection between the relatives; they knew the necessities of the patient; and they perceived as an advantage the possibility to accompany the procedures, observing possible inadequacies in the care provided (17) . Corroborating with the previous discussion, the findings of this investigation demonstrate a desire and a necessity of the relative to be near to the beloved one in the moment of emergency care, giving support and consolation, being able to observe that all necessary resources were used by the team, guaranteeing a quality care.…”
Section: Discussionmentioning
confidence: 99%